Remote sensing as a tool for natural disaster risk analysis: a bibliometric review - Román-Mireles, Amarelys (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: remote sensing as a tool is a fundamental resource that helps to develop various applications for disaster risk management.Objective: to conduct a bibliometric analysis of remote sensing as a tool for natural disaster risk analysis in Scopus between 2003 and 2023.Methods: this was a bibliometric analysis that defined the metrics of scientific production. The indicators were obtained from 409 documents chosen from the Scopus database using keywords in English (Remote sensing, natural disaster).Results: the data revealed a significant increase in the number of papers published on the topic (59,9 %) between 2019 and 2023. In addition, China (22,5 %; n=133) recorded the highest rate of scientific output, with the Chinese Academy of Sciences publishing the most (n=36). The journal Remote Sensing published 30 papers, while Natural Hazards received 720 citations, the most referenced author being Pradhan, B. (n=11 papers; 1587 citations).Conclusions: studies on this topic have increased in number, subject variation and author cooperation, as remote sensing allows data to be collected from inaccessible or hazardous regions, enabling real-time monitoring and tracking of natural phenomena.